2021
DOI: 10.1007/s10518-021-01194-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exposure spatial resolution on seismic loss estimates in regional portfolios

Abstract: The spatial resolution of exposure data has a substantial impact on the accuracy and reliability of seismic risk estimates.While several studies have investigated the influence of the geographical detail of urban exposure data in earthquake loss models, there is also a need to understand its implications at the regional scale. This study investigates the effects of exposure resolution on the European loss model and its influence on the resulting loss estimates by simulating dozens of exposure and site models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…These authors observed negligible differences in the loss estimates when alternative exposure compositions were compared within a sensitivity analysis for probabilistic risk assessment. Notably, recent studies have highlighted the importance of the statistical nature of the exposure models by forecasting its dynamic spatiotemporal evolution (Rivera et al 2020;Calderón and Silva 2021) as well as counting with efficient techniques for their spatial aggregation (Dabbeek et al 2021).…”
Section: Top-down Approach: Building Class From the Analysis Of Aggregated Datamentioning
confidence: 99%
“…These authors observed negligible differences in the loss estimates when alternative exposure compositions were compared within a sensitivity analysis for probabilistic risk assessment. Notably, recent studies have highlighted the importance of the statistical nature of the exposure models by forecasting its dynamic spatiotemporal evolution (Rivera et al 2020;Calderón and Silva 2021) as well as counting with efficient techniques for their spatial aggregation (Dabbeek et al 2021).…”
Section: Top-down Approach: Building Class From the Analysis Of Aggregated Datamentioning
confidence: 99%
“…While the focus herein has been placed on a damage estimation due to the occurrence of a scenario earthquake, which allows for the quantification of potential losses due to one specific event and, consequently, the planning of post-earthquake emergency response, the use of a building-by-building exposure model is not limited to such a calculation and can be used for larger scale regional probabilistic risk analyses as well. Apart from the question on the availability of data for larger regions, the challenge in that case lies in the identification of a resolution with which to carry out the analyses that is appropriate for the available computational resources while providing sufficiently accurate results (e.g., Dabbeek et al 2021 ), and/or the development of strategies to spatially segment the calculations in a useful and meaningful way. Some critical issues in this regard are the size of the target region and the complexity of the hazard model to be used, particularly in terms of number of end branches of the source/ground motion model logic tree.…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that the modelled and recorded residential building floor areas are highly compatible for many counties and prefectures. To further check the applicability of the modelled results in seismic risk assessment, an empirical seismic loss estimation is performed based on the intensity map of the 2008 Wenchuan M s 8.0 earthquake, the empirical loss function in Daniell (2014), and our modelled replacement value of residential buildings in Sichuan Province. By reducing the difference in unit construction price used in this paper and other studies, our estimated loss range is consistent with the loss derived from damage reports based on field investigation.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies on assessing the resolution of exposure data required for different types of natural hazards (e.g. Chen et al, 2004;Thieken et al, 2006;Bal et al, 2010;Figueiredo and Martina, 2016;Röthlisberger et al, 2018;Dabbeek et al, 2021), the 1 km × 1 km residential building stock model developed in this paper is sufficient for seismic risk assessment. However, limitations in our model are inevitable due to the assumptions and approximations em-ployed in the modelling process.…”
Section: Limitations In the Model And Directions For Future Improvementmentioning
confidence: 99%